Gap junctions and communication within the nervous system - Ramos, Adriano T.; Maiorka, Paulo C.; Dagli, Maria L. Z.; Graça, Dominguita L. (Brazilian Journal of Veterinary Pathology, 2008)
Gap junctions are sites on the cellular membrane with intercellular channels build up by twelve protein subunits called connexins. Each connected cell contributes with a hemichannel made up by six connexins subunits. This kind of connection represents and efficient way of intercellular communication in most tissues, including the nervous system. It works as a passage for ions, secondary messenger and metabolites exchange between the cells. In a complex tissue like the nervous tissue they are particularly important because they connect the various cellular types composing a panglial syncytium that performs neuronal protection and tissue homeostasis. The expression of connexins and the intercellular communication through gap junctions are crucial to regulate vital functions as cellular motility, proliferations and survival; changes in the conformational expression of connexins may be involved in diseases as Alzheimer´s disease, neoplasms, bacterial and parasitic infections, or even affect cellular groups when they occur as genetic mutations leading to functional defects of the nervous system as demyelination in the PNS (Charcot-Marie-Tooth disease), hereditary epilepsy, nonsyndromic deafness and senile cataract.